Development of the Selingkar Ijen Agropolitan Rural Area, Banyuwangi, with Ecological Resilience - Wiyono, Andri Dwi; Supranoto; Edy Wahyudi; Wheny Kristianto (Jurnal Dinamika Sosial Ekonomi, 2025)
Rural area development is an integrative development among villages in an effort to accelerate and improve the quality of services, development, and community empowerment using a participatory development approach. The governance of Rural Area Development still pays insufficient attention to local wisdom in sustainable development. This research aims to identify a local wisdom-based rural area development strategy in supporting ecological resilience. The research focuses on the Environmental Dimension in the Rural Area Development Index (IPKP) as an indicator of Ecological Resilience, and the Environmental Resilience Aspect in the Developing Village Index (IDM) as a framework for Ecological Citizenship. The research location is the Selingkar Ijen Agropolitan Area, Banyuwangi, covering 7 out of 14 villages. This research is a descriptive qualitative study using the Soft System Methodology (SSM). Data collection was carried out through observation, focused group discussions, and in-depth interviews using Planning Charrette analysis. The results indicate that the development of the Selingkar Ijen Agropolitan Area has already incorporated local wisdom in the management and utilization of the environment and natural resources. The Osing cultural local wisdom contributes to Ecological Resilience and the strengthening of Ecological Citizenship for sustainable rural area development.